2015
DOI: 10.1021/acs.jafc.5b00073
|View full text |Cite
|
Sign up to set email alerts
|

Ergostatrien-3β-ol from Antrodia camphorata Inhibits Diabetes and Hyperlipidemia in High-Fat-Diet Treated Mice via Regulation of Hepatic Related Genes, Glucose Transporter 4, and AMP-Activated Protein Kinase Phosphorylation

Abstract: This study was designed to explore the effects and mechanism of ergostatrien-3β-ol (EK100) from the submerged whole broth of Antrodia camphorata on diabetes and dyslipidemia in high fat diet (HFD)-fed mice for 12 weeks. The C57BL/6J mouse fed with a high fat diet (HFD) could induce insulin resistance and hyperlipidemia. After 8 week of induction, mice were receiving EK100 (at three dosages) or fenofibrate (Feno) or rosiglitazone (Rosi) or vehicle by oral gavage 4 weeks afterward. HFD-fed mice display increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 44 publications
(89 reference statements)
2
84
0
Order By: Relevance
“…The levels of TG and TC were measured using commercial assay kits in accordance with manufacturer directions (Triglycerides-E test and Cholesterol-E test, Wako Pure Chemical, Osaka, Japan). Aliquots of plasma samples (>25 μL) were used for insulin, leptin, and adiponectin levels by enzyme-linked immunosorbent assay (ELISA) kits (mouse insulin ELISA kit, Mercodia, Uppsala, Sweden; mouse leptin ELISA kit, Morinaga, Yokohama, Japan) as previous procedures [2426]. Percent HbA1c was measured with a Hemoglobin A 1C kit (BioSystems S.A., Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The levels of TG and TC were measured using commercial assay kits in accordance with manufacturer directions (Triglycerides-E test and Cholesterol-E test, Wako Pure Chemical, Osaka, Japan). Aliquots of plasma samples (>25 μL) were used for insulin, leptin, and adiponectin levels by enzyme-linked immunosorbent assay (ELISA) kits (mouse insulin ELISA kit, Mercodia, Uppsala, Sweden; mouse leptin ELISA kit, Morinaga, Yokohama, Japan) as previous procedures [2426]. Percent HbA1c was measured with a Hemoglobin A 1C kit (BioSystems S.A., Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Parts of liver and pancreas specimens were fixed with formalin (200 g/kg) neutral buffered solution and embedded in paraffin and sections (8 μm) were cut and stained with hematoxylin and eosin and images were photographed in accordance with previous reports [2426]. Ballooning degeneration is investigated in the liver of mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that A. camphorata exhibits many physiological and pharmacological properties. Many types of bioactive compounds have been isolated from A. camphorata, such as triterpenoids, polysaccharides, ergostanoids, succinic and maleic derivatives, benzenoids, and ubiquinone derivatives (Chang et al, 2015a;Chang, Kuo, Chang, & Kong, 2015b;Chien et al, 2008;Huang et al, 2015;Kuo, Lin, & Shih, 2015;Yen et al, 2015). Antroquinonol, an ubquinone derivative, is one of the most important bioactive compounds isolated from the mycelia and fruiting bodies of A. camphorata produced by solid-state fermentation (Lee, Lee, & Tsou, 2007).…”
Section: Introductionmentioning
confidence: 99%